The importance of understanding the maqasid of shari'ah in the development of Islamic banking and the financial system - Mohd Noor, Azman; Kamarudin, Ainatul Aqilah; Haron, Muhamad Nasir (International Islamic University Malaysia, 2016)
This paper will delienate the importance of understanding the maqasid of shari’ah in the development of Islamic banking and the financial system. The objectives of Islamic economics that are in line with the objectives of the maqasid of shari’ah need to be translated into various aspects of wealth acquisition, investment and expenses. There are specific objectives of the shari’ah in relation to financial transactions, such as the establishment of justice to the contracting parties, transparency, proper circulation of wealth and security that are the basis of the prohibitions of fraud, gambling, bribery, and all kinds of prohibitions that may render the transactions to be null and void; hence the incomes generated cannot be recognized.